Love and Money: A Theoretical and Empirical Analysis of Household Sorting and Inequality - Raquel Fernández; Nezih Guner; John Knowles (Luxembourg Income Study (LIS), 2001)
This paper examines the interactions between household matching, inequality, and per capita income. We develop a model in which agents decide whether to become skilled or unskilled, form households, consume and have children. We show that the equilibrium sorting of spouses by skill type (their correlation in education) is increasing as a function of the skill premium. In the absence of perfect capital markets, the economy can converge to dierent steady states, depending upon initial conditions. The degree of marital sorting, wage inequality, and fertility dierentials are positively correlated across steady states and negatively correlated with per capita income. We use household surveys from 34 countries to construct several measures of the skill premium and of the degree of correlation of spouses' education (marital sorting). For all our measures, we find a positive and significant relationship between the two variables.
Keywords: 330; Qualifikation; Einkommensverteilung; Fertilität; Theorie; Ehe